O ensino da medicina na Universidade de Coimbra no século XVI - Rodrigues, Isilda (2013)
The article addresses the teaching of medicine at the Universidade de Coimbra in the sixteenth century, framing it within the Portuguese and European context and highlighting the contributions of the institution's key professors - Enrique de Cuellar, Tomás Veiga, Alfonso de Guevara, and João Bravo Chamisso - along with their main works. Following a historical overview, the study analyzes the reforms of Dom Manuel I and Dom João III, the role of anatomy in the renewal of medical studies, the relation with the Discoveries, the obstacles raised by the Inquisition, medical practice at hospitals, and, lastly, the decline of medical teaching. Although they did not teach at Coimbra, reference is made to the two greatest names in sixteenth-century Portuguese medicine: Amato Lusitano and Garcia da Orta.